A Study on Documentation and Market Acceptability of Underutilized Wild Edible Crops of Kohima District, Nagaland, India - Deb, Chitta Ranjan; Khruomo, Neilazonuo; Jamir, Nangshimeren Saku (Asian Journal of Biological and Life Sciences, 2016)
Underutilized Edible Crops (UEC) has the potential for contributing to food security (nutritional/medicinal), income generation yet they are under exploited. Underutilized crops play important role in the daily lives of the rural people of Kohima, Nagaland. The present study aimed at survey and collections of UEC in Kohuma district, Nagaland. A total of 56 species of UEC belonging to 32 families are collected and identified. Based on the survey it was found that of the collected and identified species, 26 of them were wild edible fruits, 2 cereals and 30 vegetables (young leaves, shoots, stem, leafy), 1 rhizome. The use of these crops and market acceptability are studied by surveying the different markets in Kohima district, Nagaland.
Keywords: Food; Kohima district; Market acceptability; Medicine; Rural income; Underutilized wild edible crops